The Impact of Functional Jaw Orthopedics on Sleep-Related Breathing and Sleep-Related Bruxism: Case Series Study - Barbosa, Denise Fernandes; Machado Júnior, Almiro José (Sleep Science, 2025)
Sleep-related breathing disorders (SRBDs) in children can lead to obstructive sleep apnea (OSA) in adulthood and sleep-related bruxism (SRB). Neuro occlusal rehabilitation and functional jaw orthopedics (NOR-FJO) show promise in addressing SRBDs and SRB to prevent OSA progression. However, consistent evidence for managing these conditions in children is lacking, highlighting the need for early intervention to mitigate long-term complications. The present article explores NOR-FJO's effects in preventing SRBDs and their progression to OSA. We report two cases of brothers with SRBD and SRB and the case of their father with OSA. The brothers, who had overjet and overbite, were treated with NOR-FJO. The third patient had a similar history in childhood, without treatment, and developed OSA, subsequently treated with a mandibular advancement device (MAD). Timely intervention for SRBDs is essential in preventing long-term health complications, and understanding treatment strategies is crucial for early intervention.
Keywords: obstructive sleep apnea; sleep bruxism; mouth rehabilitation; orthopedics; growth and development